Feature Writing and Stylistics as Media for Local Branding: A Structural Hermeneutic Analysis - Trihastutie, Nopita (Smart Edu Center, 2024)
Feature writing is a typical journalistic product that contains a combination of news and opinion, with a storytelling style containing human interest and beautiful language. The art of feature writing is more widely understood in the context of entertaining and inspirational reading products rather than as a medium for promotion. The purpose of this study is to make a theoretical analysis to understand the art of feature writing by looking at the substance from the stylistic side that features are more than entertaining reading but are positioned as a medium for local branding. The results show that the morphology of feature writing is built on cohesion and imagery as the dominant elements of stylistics that support the delivery of meaning through the narrative structure. In conclusion, from a structural hermeneutic perspective, stylistic elements in feature writing not only build an entertaining discourse, but objective and informative, which implicitly promotes the locality as local branding.